Culturally Responsive Social Emotional Learning for International Students: Professional Development for Higher Education - Yeh, Ellen; Sharma, Rashmi; Jaiswal-Oliver, Monika; Wan, Guofang (Journal of International Students, 2021)
This qualitative study demonstrates how a culturally responsive teaching (CRT) approach builds the capacity of faculty and staff to create a social and emotional learning (SEL) environment that is conducive to success for international students. We propose a CRT–SEL model to address the increasing needs of mid-sized universities with emerging international students. The findings from 14 faculty and staff participants point to professional development strategies that can help reduce or remove barriers for working with international students. This study highlights the need to build upon the CRT and SEL tenets and align them with the existing support networks within the mid-size higher education institutions for classroom learning and off-campus activities to bolster international students’ overall success. The results also indicate the faculty and staff’s varying priorities and diverging trajectories.